Efficient Synthesis of Quaternised Guar Gum using Tri‐alkylamine and Epichlorohydrin Condensate by Taguchi L9 Orthogonal Array. Issue 44 (22nd November 2022) - Tyagi, Rakhi; Kumar, Vineet; Sharma, Pradeep
Abstract: Glycidyltrimethylammonium chloride (GLYTAC) is an efficient quaternizing reagent, easy to synthesize, and causes lesser degradation to the polymer backbone than other reagents. Quaternization of guar gum was carried out using condensate of trimethylamine and epichlorohydrin as etherifying reagents adopting Taguchi's L9 orthogonal array design of experiment to optimize the reaction conditions to attain a higher degree of substitution (DS). The set of optimized levels of selected control factors are as follows; 2.5 mL and 1.2 g of condensate and sodium hydroxide respectively at 30 °C and time 6 h. The DS of the quaternized derivative prepared under optimized reaction conditions was determined as 0.046. The appearance of an additional signal at 3.06 ppm and 54.62 in 1 H and 13 C and the corresponding cross signal inHSQC ( 1 H− 13 C) confirmed the synthesis of quaternized guar gum. The study demonstrated that Taguchi L9 orthogonal array is a reliable statistical approach for efficient and green synthesis of quaternized derivatives. Abstract : Synthesis of quaternized guar gum was carried out by treatment with condensate of trimethylamine and epichlorohydrin under the catalytic action of sodium hydroxide. The reaction conditions were optimized using the Taguchi L9 statistical design. The maximum DS of 0.046 was obtained for the optimized derivative. The quaternized product was characterized by 1 H, 13 C and HSQC spectroscopic methods.